Non-noble metal difunctional electrolyzed water catalyst and preparation method and application thereof
By loading molybdenum carbide and iron-cobalt layered double hydroxides on the foam metal substrate, a heterojunction of FeCoMo nanoparticles was formed to prepare a non-precious metal dual-function electrolytic catalyst with high catalytic performance and low cost, solving the problem of insufficient reactivity and cost of existing catalysts, and achieving high efficiency and economicality of electrolyzing hydrogen production.
Patent Information
- Application Number
- CN202510042718.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-15
AI Technical Summary
The existing electrolytic water catalysts have shortcomings in terms of reactivity and cost, which limits the efficiency and economicality of electrolytic water hydrogen production.
By uniformly loading molybdenum carbide and iron-cobalt layered double hydroxides or their derivatives on the foam metal substrate, heterojunctions of FeCoMo nanoparticles with irregular shapes were formed, and non-precious metal bifunctional electrolytic water catalysts were prepared by high-temperature calcination, electrodeposition and oxidation pretreatment.
A non-precious metal dual-function electrolytic catalyst with high catalytic performance and low cost is achieved, which is better than traditional precious metal catalysts and exhibits lower overpotentials and high stability in the process of electrolyzing hydrogen production.
Smart Images

Figure CN119824468A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of hydrogen production by water electrolysis catalyst, and specifically relates to a non-precious metal bifunctional water electrolysis catalyst and its preparation method and application. The present invention also belongs to the field of new energy materials and technologies, and specifically relates to catalyst design and preparation technology in the process of water electrolysis hydrogen production. More precisely, it is a bifunctional water electrolysis catalyst for non-precious metal materials and its preparation method, which aims to improve the efficiency and economy of water electrolysis hydrogen production through innovative material combinations and synthesis strategies, thereby promoting the sustainable development of the hydrogen energy industry. Background Art
[0002] With the excessive use of fossil fuels, air pollution and global warming are becoming more and more serious. In this context, it is urgent to explore green, pollution-free and sustainable energy to replace traditional fossil fuels. Among them, hydrogen energy is considered to be the best choice to meet the future needs of human production and life due to its environmental protection and renewability. However, most hydrogen is produced by burning fossil fuels, accompanied by the release of greenhouse gases. Among the many hydrogen production technologies, electrocatalytic water decomposition has attracted widespread attention as an efficient, low-pollution and environmentally friendly way of hydrogen production. Electrocatalytic water decomposition is a common green and sustainable hydrogen production reaction accompanied by hydrogen evolution reaction and oxygen evolution reaction. Although water electrolysis theoretically has a good possibility of producing high-purity hydrogen, its slow kinetics affects the catalytic efficiency.
[0003] At present, water electrolysis catalysts are mainly divided into two categories: non-precious metals and precious metals. Non-precious metal catalysts mainly refer to transition metal-based compounds and carbon-based catalysts. This type of catalyst has low cost but limited activity. Although precious metal (platinum, ruthenium and iridium, etc.) catalysts have good catalytic performance for hydrogen and oxygen evolution, their low reserves and high prices still pose great challenges to their widespread application, which greatly increases the cost of hydrogen production by water electrolysis. In this context, the research and development of non-precious metal catalysts has become a research hotspot in the field of hydrogen production by water electrolysis. Non-precious metal catalysts are regarded as potential alternatives to precious metal catalysts due to their advantages such as low cost and abundant sources. However, non-precious metal catalysts often have shortcomings in terms of activity, stability and selectivity, which limits their practical application.
[0004] In recent years, with the continuous development of nanotechnology, materials science and electrochemical technology, the research on non-precious metal bifunctional water electrolysis catalysts has made significant progress. By finely regulating the composition, structure and morphology of the catalysts and optimizing the preparation process, researchers have successfully developed a series of non-precious metal bifunctional catalysts with high activity, high stability and good selectivity. These catalysts have shown excellent performance in the process of hydrogen production by water electrolysis, providing strong support for promoting the sustainable development of the hydrogen energy industry.
[0005] For example, CN117626338A discloses a nano flower-shaped three-dimensional porous composite electrolytic water catalyst and its preparation method and application, and discloses its preparation method as follows: S1: pickling and hydrophilizing nickel foam, washing and drying for standby use; S2: mixing and stirring nickel salt, molybdenum salt, inhibitor, urea, water, then adding the treated nickel foam in S1 for a hydrothermal reaction, taking out the reactant, washing and drying, and then calcining once to obtain the primary product; S3: mixing and stirring vanadium salt and urea, then adding the primary product in S2 for a secondary hydrothermal reaction, taking out the reactant, washing and drying, and then calcining twice to obtain a nano flower-shaped three-dimensional porous composite electrolytic water catalyst, which is used for electrolysis of water to produce hydrogen. However, its preparation involves multiple steps, the process is relatively complicated, and the reaction conditions need to be precisely controlled, resulting in low productivity, which is not conducive to large-scale industrial production. The variety of raw materials increases the complexity of raw material procurement and management, and also affects production costs. That is, although the use of non-precious metal catalysts reduces the composition, compared with simple preparation methods, this method has many types of raw materials, a complex preparation process, and a relatively high cost. The catalyst prepared by this method shows a certain performance improvement in hydrogen production by electrolysis of water, but there is still room for further optimization, such as improving catalytic activity and reducing overshoot.
[0006] In summary, the research and development of non-precious metal bifunctional electrocatalysts for water electrolysis is one of the important research directions in the field of hydrogen production by water electrolysis. Therefore, how to improve the activity, stability and life of the catalyst has become a hot topic and difficulty in research, and designing bifunctional non-precious metal electrocatalysts with high catalytic performance is the key to promoting the practical application of electrocatalytic water splitting technology. Summary of the invention
[0007] In view of the problems of low reaction activity and high cost of existing hydrogen production catalysts, the present invention provides a non-precious metal bifunctional water electrolysis catalyst with high catalytic performance and low cost and a preparation method thereof.
[0008] The technical solution of the present invention is a non-precious metal bifunctional water electrolysis catalyst, which uses foam metal as a matrix, and evenly loads molybdenum carbide, iron-cobalt layered double hydroxide or its derivatives on the matrix. The molybdenum carbide and the iron-cobalt layered double hydroxide or its derivatives are in contact and doped with each other to generate an irregularly shaped FeCoMo nanoparticle heterojunction.
[0009] The derivative of the iron-cobalt layered double hydroxide is an electrochemical oxide of an iron-cobalt layered double hydroxide (such as (EO)FeCo-LDH / Mo2C@Cu Foam shown in the embodiment), or a chlorine-doped iron-cobalt layered double hydroxide (such as Cl / FeCo-LDH / Mo2C@Cu Foam shown in the embodiment), or an electrochemical oxide of a chlorine-doped iron-cobalt layered double hydroxide (such as (EO)Cl / FeCo-LDH / Mo2C@Cu Foam shown in the embodiment). Part of the chloride ions are removed by electrochemical oxidation to increase the voids and surface area, and the electrochemical oxide of the chlorine-doped iron-cobalt layered double hydroxide is preferred.
[0010] The interlayer distance of the iron-cobalt layered double hydroxide or its derivative is 0.1-0.6 nm, preferably 0.1-0.4 nm, and more preferably 0.15-0.4 nm.
[0011] The molybdenum carbide is in the form of nanoparticles, with a size of 0.1-0.5 nm, preferably 0.1-0.3 nm, more preferably 0.15-0.3 nm, and even more preferably 0.2-0.3 nm.
[0012] The chlorine doped in the iron-cobalt layered double hydroxide or its derivatives exists in the form of chloride, including but not limited to alkali metal chlorides such as sodium chloride and potassium chloride, and / or alkaline earth metal chlorides such as magnesium chloride, and / or transition metal chlorides such as iron chloride, zinc chloride, titanium chloride, and / or other metal chlorides such as aluminum chloride, preferably sodium chloride. The chloride is a nanoparticle with a size of 0.1-0.5nm, preferably 0.1-0.3nm, more preferably 0.15-0.3nm, and even more preferably 0.2-0.3nm.
[0013] The present invention provides a non-precious metal bifunctional water electrolysis catalyst containing Mo2C, and / or iron-cobalt layered double hydroxide or its derivatives, and / or chloride, preferably sodium chloride, chlorine-doped iron-cobalt layered double hydroxide electrochemical oxide and molybdenum carbide.
[0014] The foam metal is a foam material with a skeleton composed of any one or any combination of metals and alloys such as Cu, Ni, Al, Zn, Li, Fe, Ag, Au, Ca, W, NiCrFe, ZnCu, NiCu, NiCrW, NiFe, etc., and is preferably foam copper.
[0015] The present invention provides a method for preparing a non-precious metal bifunctional water electrolysis catalyst, the steps comprising:
[0016] Using an aqueous solution containing cobalt ions and iron ions as an electrolyte and a foam metal precursor loaded with molybdenum carbide as a working electrode, in a standard three-electrode system, a constant voltage method is used to perform cathode electrodeposition on the foam metal precursor loaded with molybdenum carbide to deposit iron-cobalt layered double hydroxide to obtain FeCo-LDH / Mo2C@Foam; or,
[0017] Chloride ions were added as electrolyte to an aqueous solution containing cobalt ions and iron ions, and the foam metal loaded with molybdenum carbide was used as a precursor for cathode electrodeposition to deposit chlorine-doped iron-cobalt layered double hydroxide to obtain Cl / FeCo-LDH / Mo2C@Foam.
[0018] The steps of preparing the foam metal precursor loaded with molybdenum carbide include:
[0019] 1) placing a foamed metal in an aqueous solution containing ammonium molybdate, urea and citric acid, and drying the solution to obtain a foamed metal covered with a gel precursor;
[0020] 2) calcining the foam metal covering the gel precursor in a nitrogen environment to obtain a foam metal precursor loaded with molybdenum carbide.
[0021] In step 1), the molar ratio of ammonium molybdate, urea and citric acid is 1:150-450:30-150, preferably 1:180-220:40-80, more preferably 1:190-210:40-70, more preferably 1:200-210:60-70, further preferably 1:208-209:65-66, and as a preferred embodiment of the present invention, it is 1:208.5-209:65-65.5; the concentration of ammonium molybdate is 0.01-0.03 mol / L, preferably 0.015-0.02 mol / L, and further preferably 0.017-0.018 mol / L.
[0022] The ammonium molybdate is any one or any combination of ammonium dimolybdate, ammonium tetramolybdate, ammonium heptamolybdate, ammonium octamolybdate, etc., preferably ammonium heptamolybdate.
[0023] In step 1), drying is performed at 70°C-80°C for 6-9h.
[0024] In step 1), the foam metal is first cleaned by ultrasonic cleaning in acetone, dilute hydrochloric acid, water, ethanol, and water for 10 minutes in sequence, and then dried.
[0025] In step 1), the foam metal is a foam material with a skeleton of any one or any combination of metals and alloys such as Cu, Ni, Al, Zn, Li, Fe, Ag, Au, Ca, W, NiCrFe, ZnCu, NiCu, NiCrW, NiFe, etc., preferably foam copper.
[0026] In step 2), the gel precursor evenly covers the metal foam.
[0027] In step 2), the temperature is raised to 800° C. at a heating rate of 5° C. / min and kept at that temperature for 3 h for calcination.
[0028] The molar ratio of cobalt ions to iron ions in the electrolyte is 1:0.5-2, more preferably 1:0.8-1.5, more preferably 1:0.8-1.2, and more preferably 1:1; the concentration of cobalt ions is 0.04-0.06 mol / L, more preferably 0.045-0.055 mol / L, and more preferably 0.05 mol / L; when the electrolyte contains chloride ions, the molar ratio of cobalt ions to chloride ions is 1:0.1-0.5, preferably 1:0.2.
[0029] The cobalt ions are derived from cobalt salts, which include but are not limited to cobalt chloride, cobalt iodide, cobalt bromide, cobalt nitrate, cobalt sulfate, cobalt carbonate, cobalt phosphate, cobalt silicate, cobalt oxalate, etc. Cobalt chloride includes but is not limited to anhydrous cobalt chloride, cobalt chloride dihydrate, cobalt chloride tetrahydrate, cobalt chloride hexahydrate, etc. Cobalt nitrate includes but is not limited to hexahydrated cobalt nitrate, cobalt sulfate includes anhydrous cobalt sulfate, cobalt sulfate heptahydrate, cobalt sulfate octahydrate, etc. Cobalt carbonate includes but is not limited to anhydrous cobalt carbonate, cobalt carbonate hexahydrate, etc. Cobalt phosphate includes but is not limited to anhydrous cobalt phosphate, cobalt phosphate octahydrate, etc. Cobalt silicate includes but is not limited to cobalt metasilicate, cobalt orthosilicate, etc. Cobalt oxalate includes but is not limited to divalent cobalt oxalate, trivalent cobalt oxalate, etc. More preferably, cobalt nitrate hexahydrate.
[0030] The iron ions are derived from iron salts, including but not limited to ferric chloride, polyferric sulfate, polyferric chloride, ferric nitrate, ferric hydroxide, etc., ferric chloride includes but not limited to anhydrous ferric chloride, ferric chloride hexahydrate, ferric chloride trihydrate, etc., ferric nitrate includes but not limited to anhydrous ferric nitrate, ferric nitrate nonahydrate, etc., ferric sulfate includes but not limited to anhydrous ferric sulfate, ferric sulfate nonahydrate, etc. Preferably, ferric nitrate nonahydrate.
[0031] The chloride ions are derived from chlorides, including but not limited to alkali metal chlorides such as sodium chloride and potassium chloride, and / or alkaline earth metal chlorides such as magnesium chloride, and / or transition metal chlorides such as iron chloride, zinc chloride, titanium chloride, and / or other metal chlorides such as aluminum chloride, preferably sodium chloride.
[0032] In the standard three-electrode system using the constant voltage method, a platinum wire is used as a counter electrode and a saturated calomel electrode is used as a reference counter electrode.
[0033] In the standard three-electrode system using the constant voltage method, the voltage is -1.0V.
[0034] The invention provides a method for preparing a non-precious metal bifunctional water electrolysis catalyst, which further comprises the following steps: using an alkaline aqueous solution as an electrolyte, using FeCo-LDH / Mo2C@Foam or Cl / FeCo-LDH / Mo2C@Foam as a working electrode, and performing oxidation pretreatment by cyclic voltammetry in a standard three-electrode system to prepare (EO)FeCo-LDH / Mo2C@Foam or (EO)Cl / FeCo-LDH / Mo2C@Foam.
[0035] In the standard three-electrode system using cyclic voltammetry, a carbon rod is used as a counter electrode and a saturated calomel electrode is used as a reference counter electrode.
[0036] In the standard three-electrode system using cyclic voltammetry, the voltage range of cyclic voltammetry is 1.26-1.86V.
[0037] In the standard three-electrode system using cyclic voltammetry, the alkaline aqueous solution is a 0.5-2 mol / L potassium hydroxide aqueous solution or a sodium hydroxide aqueous solution, and more preferably a 1 mol / L potassium hydroxide aqueous solution or a sodium hydroxide aqueous solution.
[0038] In the standard three-electrode system using cyclic voltammetry, the oxidation pretreatment was performed 20 times.
[0039] The non-precious metal bifunctional water electrolysis catalyst prepared by the present invention contains Mo2C, and / or iron-cobalt layered double hydroxide or its derivatives, and / or chloride, preferably sodium chloride, electrochemical oxide of chlorine-doped iron-cobalt layered double hydroxide and molybdenum carbide.
[0040] The interlayer distance of the iron-cobalt layered double hydroxide or its derivative is 0.1-0.6 nm, preferably 0.1-0.4 nm, and more preferably 0.15-0.4 nm.
[0041] The molybdenum carbide is in the form of nanoparticles, with a size of 0.1-0.5 nm, preferably 0.1-0.3 nm, more preferably 0.15-0.3 nm, and even more preferably 0.2-0.3 nm.
[0042] The iron-cobalt layered double hydroxide or its derivatives are doped with chlorine, and the doped chlorine exists in the form of chloride, including but not limited to alkali metal chlorides such as sodium chloride and potassium chloride, and / or alkaline earth metal chlorides such as magnesium chloride, and / or transition metal chlorides such as iron chloride, zinc chloride, titanium chloride, and / or other metal chlorides such as aluminum chloride, preferably sodium chloride. The chloride is a nanoparticle with a size of 0.1-0.5nm, preferably 0.1-0.3nm, more preferably 0.15-0.3nm, and even more preferably 0.2-0.3nm.
[0043] The non-noble metal bifunctional water electrolysis catalyst prepared by the present invention can not only perform oxygen evolution reaction, but also perform hydrogen evolution reaction, and can be used to prepare oxygen and / or hydrogen.
[0044] Compared with the prior art, the advantages of the present invention are:
[0045] (1) The present invention mainly utilizes the methods of high temperature calcination, electrodeposition and oxidation pretreatment to grow lamellar and granular FeCoMo heterostructures on a foam copper substrate ( Figure 1 ), forming an efficient non-precious metal catalyst, denoted as (EO)Cl / FeCo-LDH / Mo2C@Cu Foam. The HER current density of the prepared catalyst under 1M KOH alkaline conditions was measured by electrochemical method to be 10 mA cm -2 The overpotential is only 59 mV, and the same OER current density is 10 mA cm -2 The overpotential is only 159mV. This indicates that the non-precious metal bifunctional water electrolysis catalyst has a low overpotential, and the catalyst has excellent bifunctional catalytic performance in water electrolysis, and is superior to precious metal catalysts such as Pt / C and RuO2 / IrO2. When it is used as a bifunctional water electrolysis catalyst (hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) are carried out at the cathode and anode respectively), ideally only 1.49V is required to achieve water decomposition, which is lower than other bifunctional catalysts of the same type, indicating that the bifunctional electrocatalyst has excellent overall water splitting performance.
[0046] That is, the present invention deeply studies the relationship between the composition, structure and performance of the catalyst, and optimizes the performance of the catalyst by adjusting the proportion of metal elements, introducing new active sites or changing the morphology of the catalyst, especially improving the catalytic activity and reducing the overpotential, so as to meet the higher requirements of water electrolysis hydrogen production applications.
[0047] (2) The present invention prepares the catalyst through simple high-temperature calcination, electrodeposition and oxidation pretreatment steps, and the metals involved are all non-precious metal materials and their salts, which reduces the cost of its preparation and greatly improves the cost of hydrogen production by electrolysis of water. Its catalytic performance such as HER, OER, and overall water splitting has been improved to a certain extent, which is better than most water electrolysis catalysts.
[0048] That is, the present invention develops a more concise and efficient method for preparing a non-precious metal bifunctional catalyst, which reduces the preparation steps and the dependence on precise reaction conditions, thereby improving production efficiency and facilitating large-scale industrial production. Under the premise of ensuring the performance of the catalyst, by simplifying the preparation process and reducing the types of raw materials, the cost is further reduced, so that the non-precious metal bifunctional catalyst has stronger market competitiveness in the fields of water electrolysis and hydrogen production.
[0049] (3) The present invention explores the synergistic mechanism between different metal elements, introduces more non-precious metals, and enhances the synergistic effect between metals through reasonable metal combination and structural design, increasing the number and types of active sites, thereby improving the catalytic efficiency and stability of the catalyst. Through innovative material combination and synthesis strategies, the efficiency and economy of hydrogen production by water electrolysis are improved, thereby promoting the sustainable development of the hydrogen energy industry.
[0050] In summary, the non-precious metal bifunctional catalyst of the present invention aims to provide a more efficient, economical and environmentally friendly catalyst solution for fields such as water electrolysis and hydrogen production by simplifying the preparation process, reducing costs, optimizing catalyst performance and enhancing metal synergy. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] Figure 1 This is a flow chart of the preparation of the (EO)Cl / FeCo-LDH / Mo2C@Cu Foam non-precious metal catalyst in Example 1. EO stands for Electrochemical oxidation.
[0052] Figure 2 This is a scanning electron microscope image of the surface morphology of the (EO)Cl / FeCo-LDH / Mo2C@Cu Foam non-precious metal catalyst in Example 1.
[0053] Figure 3 This is the transmission electron microscopy (TEM) image of the (EO)Cl / FeCo-LDH / Mo2C@Cu Foam non-precious metal catalyst in Example 1.
[0054] Figure 4 This is a high-resolution transmission electron microscopy (HRTEM) image of the (EO)Cl / FeCo-LDH / Mo2C@Cu Foam non-precious metal catalyst in Example 1. The red dashed line in the figure is the heterogeneous interface, the red circle is the defect, the FeCo-LDH interlayer spacing is 0.379nm (006), 0.759nm (003), 0.164nm (0111), FeCo-LDH doped with NaCl nanoparticles: 0.281nm (200), FeCo-LDH doped with Mo2C nanoparticles: 0.261nm (100).
[0055] Figure 5 This is the XRD spectrum of the (EO)Cl / FeCo-LDH / Mo2C@Cu Foam non-precious metal catalyst in Example 1.
[0056] Figure 6The linear voltammetry (LSV) curves of the samples prepared in Example 1 and Comparative Examples 1, 2, and 3 in HER test in 1 M KOH solution.
[0057] Figure 7 It is the linear voltammetry (LSV) curve of the OER test of the samples prepared in Example 1 and Comparative Examples 1, 2, and 3 in 1M KOH solution.
[0058] Figure 8 The (EO)Cl / FeCo-LDH / Mo2C@Cu Foam non-precious metal catalyst in Example 1 was measured by chronopotentiometry at 10 mA cm in 1 M KOH solution. -2 HER stability curve measured at a current density of .
[0059] Fig. 9 The (EO)Cl / FeCo-LDH / Mo2C@Cu Foam non-precious metal catalyst in Example 1 was measured by chronopotentiometry at 10 mA cm in 1 M KOH solution. -2 OER stability curve measured at a current density of .
[0060] Fig.10 LSV curve of water electrolysis using (EO)Cl / FeCo-LDH / Mo2C@Cu Foam non-precious metal catalyst as a dual-electrode system. DETAILED DESCRIPTION
[0061] Example 1: Figure 1 As shown, a method for preparing a non-precious metal bifunctional water electrolysis catalyst, the operating steps are as follows:
[0062] Step 1: Take a 1cm×2cm copper foam, and ultrasonically clean the copper foam for 10 minutes in the order of acetone, dilute hydrochloric acid, water, ethanol, and water, and then wash and dry to obtain pretreated copper foam (clean copper foam is obtained by pretreatment). Add 0.148g of ammonium heptamolybdate, 1.5g of urea, and 1.5g of citric acid to 7mL of water to form a mixed solution. Soak the copper foam in the solution to form a mixture. Put the mixture into an oven and dry it at 80°C for 8h to form a gel precursor.
[0063] In this step, copper foam (Cu Foam) is used as a carrier, which not only provides good conductivity and stability, but also promotes the penetration of electrolyte and the release of hydrogen products through its porous structure.
[0064] The amount of urea and citric acid used in step 1 can be increased to 3 g. The gel precursor can be prepared by the above operation according to the ratio of 3 g urea and 1.5 g citric acid, or 3 g urea and 3 g citric acid, or 1.5 g urea and 3 g citric acid.
[0065] Step 2: The precursor is evenly covered with copper foam, placed in a crucible, and heated at 800°C for 3 hours at a heating rate of 5°C / min under N2 conditions. Finally, a molybdenum carbide-loaded copper foam precursor catalyst, namely Mo2C@Cu Foam precursor catalyst, is formed.
[0066] Step 3: 0.05M cobalt nitrate hexahydrate, 0.01M sodium chloride and 0.05M ferric nitrate nonahydrate were mixed to form a uniform solution. In the Chenhua electrochemical workstation, a standard three-electrode system (Mo2C@Cu Foam precursor catalyst as the working electrode, platinum wire as the counter electrode, and saturated calomel electrode as the reference electrode) was used. The precursor catalyst was cathode-electrodeposited at -1.0V for 4800s using a constant voltage method to generate the catalyst semi-finished product Cl / FeCo-LDH / Mo2C@Cu Foam. In this step, a chlorine-doped FeCo LDH structure was generated on the precursor catalyst by electrodeposition. In this step, the chlorine-doped iron-cobalt layered double hydroxide grows directly on the Mo2C nanoparticles to form a clear layered structure, which not only provides a larger surface area and more active sites for the redox reaction, but also has a larger void, which is conducive to rapid mass transfer and electrolyte penetration, and incubates the catalyst with high catalytic performance.
[0067] Iron and cobalt bimetallics are introduced into the iron-cobalt layered double hydroxide to add new active sites, and iron and cobalt work synergistically in the catalytic reaction to promote the water electrolysis process and improve the HER and OER catalytic performance of the catalyst.
[0068] The molar mass ratio of iron ions to cobalt ions in step 3 can also be changed to 1:2 or 2:1, and the above operation is used to generate a chlorine-doped FeCo LDH structure on the precursor catalyst.
[0069] Step 4: This step is also carried out in the Chenhua electrochemical workstation. Using a standard three-electrode system (the catalyst semi-finished product prepared in step 3 is used as the working electrode, the carbon rod is used as the counter electrode, and the saturated calomel electrode is used as the reference electrode), the catalyst semi-finished product generated in step 3 is placed in 1M KOH and oxidized 20 times in the range of 1.26-1.86V to generate (EO)Cl / FeCo-LDH / Mo2C@Cu Foam. This step removes some chloride ions and introduces vacancies and defects through the oxidation pretreatment step, further improving the catalytic performance.
[0070] Comparative Example 1:
[0071] The method of Example 1 is followed, except that step 4 is not performed. The specific steps are as follows:
[0072] Step 1: Take a 1cm×2cm copper foam, and ultrasonically clean the copper foam for 10 minutes in the order of acetone, dilute hydrochloric acid, water, ethanol, and water, and then wash and dry to obtain the pretreated copper foam. Add 0.148g of ammonium heptamolybdate, 1.5g of urea, and 1.5g of citric acid to 7mL of water to form a mixed solution. After the solution is mixed evenly, add the copper foam to soak the copper foam in the solution to form a mixture. Put the mixture into an oven and dry it at 80°C for 8h to form a gel precursor.
[0073] Step 2: The precursor is evenly covered with the copper foam, placed in a crucible, and kept at 800°C for 3 hours at a heating rate of 5°C / min under N2 conditions. Finally, a molybdenum carbide-loaded copper foam precursor catalyst is formed.
[0074] Step 3: 0.05M cobalt nitrate hexahydrate, 0.01M sodium chloride and 0.05M ferric nitrate nonahydrate were mixed to form a uniform solution. The precursor catalyst was cathode electrodeposited at -1.0V for 4800s using a constant voltage method. Cl / FeCo-LDH / Mo2C@Cu Foam was generated.
[0075] Comparative Example 2:
[0076] The method of comparative example 1 is used for implementation, except that sodium chloride is not added to the electrodeposition solution in step 3. The specific operation steps are as follows:
[0077] Step 1: Take a 1cm×2cm copper foam, and ultrasonically clean the copper foam for 10 minutes in the order of acetone, dilute hydrochloric acid, water, ethanol, and water, and then wash and dry to obtain the pretreated copper foam. Add 0.148g of ammonium heptamolybdate, 1.5g of urea, and 1.5g of citric acid to 7mL of water to form a mixed solution. After the solution is mixed evenly, put the copper foam in to soak the copper foam in the solution to form a mixture. Put the mixture into an oven and dry it at 80℃ for 8h to form a gel precursor.
[0078] Step 2: The precursor is evenly covered with the copper foam, placed in a crucible, and kept at 800°C for 3 hours at a heating rate of 5°C / min under N2 conditions. Finally, a molybdenum carbide-loaded copper foam precursor catalyst is formed.
[0079] Step 3: 0.05M cobalt nitrate hexahydrate and 0.05M ferric nitrate nonahydrate were mixed to form a uniform solution. The precursor catalyst was cathode electrodeposited at -1.0V for 4800s using a constant voltage method to generate a catalyst semi-finished product.
[0080] Step 4: The catalyst semi-finished product generated in step 3 was placed in 1M KOH and subjected to 20 oxidation pretreatments in the range of 1.26-1.86V to generate (EO)FeCo-LDH / Mo2C@Cu Foam.
[0081] Comparative Example 3:
[0082] The method of comparative example 1 is used for implementation, except that steps 3 and 4 are not performed. The specific operation steps are as follows:
[0083] Step 1: Take a 1cm×2cm copper foam, and ultrasonically clean the copper foam for 10 minutes in the order of acetone, dilute hydrochloric acid, water, ethanol, and water, and then wash and dry to obtain the pretreated copper foam. Add 0.148g of ammonium heptamolybdate, 1.5g of urea, and 1.5g of citric acid to 7mL of water to form a mixed solution. After the solution is mixed evenly, add the copper foam to soak the copper foam in the solution to form a mixture. Put the mixture into an oven and dry it at 80°C for 8h to form a gel precursor.
[0084] Step 2: The precursor is evenly covered with the copper foam, placed in a crucible, and heated at 800°C for 3 hours at a heating rate of 5°C / min under N2 conditions. Finally, the Mo2C@Cu Foam catalyst is formed.
[0085] The non-precious metal bifunctional water electrolysis catalyst prepared in the present invention was characterized by scanning electron microscopy, transmission electron microscopy and X-ray diffraction, and the electrochemical performance of the catalyst obtained in Example 1 was tested in a three-electrode system using an electrochemical workstation. The characterization and test results are shown in Figures 2 to 8 shown.
[0086] Can be obtained from Figure 2 It can be seen that the surface of the non-precious metal bifunctional water electrolysis catalyst prepared in Example 1 is uniformly covered with lamellar LDH structures, and there are also some irregularly shaped nanoparticle heterogeneous structures. These structures not only provide a larger surface area and more active sites for redox reactions, but also have more pores, which are conducive to rapid mass transfer and electrolyte penetration, thus giving it high electrocatalytic performance. Figure 3-4 Different structures can also be seen in the transmission electron microscopy images. Figure 2 The results are consistent. Figure 5 It can be seen that there are multiple different phases on the catalyst surface of (EO)Cl / FeCo-LDH / Mo2C@CuFoam obtained in Example 1, which are composed of NaCl, FeCo-LDH and Mo2C phases.
[0087] Depend on Figure 6It can be seen that the catalytic hydrogen evolution performance of the (EO)Cl / FeCo-LDH / Mo2C@Cu Foam catalyst obtained in Example 1 is better than that of the catalysts prepared in Comparative Examples 1, 2 and 3. The HER current density of the catalyst obtained in Example 1 under alkaline conditions is 10 mA cm -2 The overpotential is only 59mV. Figure 7 It can be seen that the catalytic oxygen evolution performance of the non-precious metal bifunctional water electrolysis catalyst obtained in Example 1 is better than that of the catalysts prepared in Comparative Examples 1, 2 and 3. The catalyst obtained in Example 1 has an OER current density of 10 mA cm under alkaline conditions. -2 The overpotential is only 159 mV. This indicates that the non-precious metal bifunctional water electrolysis catalyst prepared in Example 1 has a low overpotential and the catalyst has excellent bifunctional catalytic performance for water electrolysis.
[0088] Figure 8 and Fig. 9 The long-term chronoamperometric test curves of HER and OER of the non-precious metal bifunctional water electrolysis catalyst obtained in Example 1 in 1M KOH electrolyte are shown in the it curve. It can be seen from the it curve in the figure that the current density of the catalyst can be maintained at 10 mA cm for at least 12 hours. -2 There is almost no attenuation, indicating its excellent stability in both HER and OER catalytic reactions. Fig.10 The LSV curve of water electrolysis of the two-electrode system is 10 mA / cm 2 The corresponding potential is only 1.49 V, indicating that the catalyst can be used as a bifunctional water electrolysis catalyst in water electrolysis and has excellent water electrolysis performance.
[0089] It should be pointed out that the above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology of this project to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A non-precious metal bifunctional water electrolysis catalyst, characterized in that: The foamed metal is used as a matrix, and molybdenum carbide, iron-cobalt layered double hydroxide or its derivatives are uniformly loaded on the matrix. The molybdenum carbide and the iron-cobalt layered double hydroxide or its derivatives are in contact and doped with each other to generate an irregularly shaped FeCoMo nanoparticle heterojunction.
2. A non-precious metal bifunctional water electrolysis catalyst according to claim 1, characterized in that: The derivative of the iron-cobalt layered double hydroxide is an electrochemical oxide of the iron-cobalt layered double hydroxide, or a chlorine-doped iron-cobalt layered double hydroxide, or an electrochemical oxide of a chlorine-doped iron-cobalt layered double hydroxide.
3. A method for preparing a non-precious metal bifunctional water electrolysis catalyst, characterized in that the steps include: Using an aqueous solution containing cobalt ions and iron ions as an electrolyte and a foam metal precursor loaded with molybdenum carbide as a working electrode, in a standard three-electrode system, a constant voltage method is used to perform cathode electrodeposition on the foam metal precursor loaded with molybdenum carbide to deposit iron-cobalt layered double hydroxide to obtain FeCo-LDH / Mo2C@Foam; or, Chloride ions were added as electrolyte to an aqueous solution containing cobalt ions and iron ions, and cathode electrodeposition was carried out on a foam metal precursor loaded with molybdenum carbide to deposit chlorine-doped iron-cobalt layered double hydroxide to obtain Cl / FeCo-LDH / Mo2C@Foam.
4. The preparation method according to claim 3, characterized in that: The molar ratio of cobalt ions to iron ions in the electrolyte is 1:0.5-2, and the concentration of cobalt ions is 0.04-0.06 mol / L; when the electrolyte contains chloride ions, the molar ratio of cobalt ions to chloride ions is 1:0.1-0.
5.
5. The preparation method according to claim 3 or 4, characterized in that: The steps of preparing the foam metal precursor loaded with molybdenum carbide include: 1) placing a foamed metal in an aqueous solution containing ammonium molybdate, urea and citric acid, and drying the solution to obtain a foamed metal covered with a gel precursor; 2) calcining the foam metal covering the gel precursor in a nitrogen environment to obtain a foam metal precursor loaded with molybdenum carbide.
6. The preparation method according to claim 5, characterized in that: In step 1), the molar ratio of ammonium molybdate, urea and citric acid is 1:150-450:30-150, and the concentration of ammonium molybdate is 0.01-0.03 mol / L.
7. The preparation method according to claim 3 or 4, characterized in that: The following steps are also included: Using alkaline aqueous solution as electrolyte and FeCo-LDH / Mo2C@Foam or Cl / FeCo-LDH / Mo2C@Foam as working electrode, cyclic voltammetry was used in a standard three-electrode system to carry out oxidation pretreatment to prepare (EO)FeCo-LDH / Mo2C@CuFoam or (EO)Cl / FeCo-LDH / Mo2C@Foam.
8. The preparation method according to claim 7, characterized in that: The alkaline aqueous solution is a 0.5-2M potassium hydroxide aqueous solution or a sodium hydroxide aqueous solution.
9. The preparation method according to claim 7, characterized in that: The oxidation pretreatment voltage condition is 1.26-1.86V.
10. Use of the non-precious metal bifunctional water electrolysis catalyst according to claim 1 or 2 in the preparation of hydrogen and / or oxygen.
Citation Information
Patent Citations
Nanometer flower-ball-shaped three-dimensional porous composite electrolyzed water catalyst as well as preparation method and application thereof
CN117626338A